Polyvinyl acetal resin, conductive paste and multilayer ceramic capacitor
By using polyvinyl acetal resin of specific structural units, the bleeding problem caused by too low viscosity of conductive powder printing adhesive is solved, and the adhesive with high viscosity and good taper characteristics is achieved, and the printing accuracy of multi-layer ceramic capacitors is improved.
Patent Information
- Application Number
- JP2024111677
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2044-07-02
AI Technical Summary
In the prior art, when polyvinyl acetal resin is used as the conductive powder printing adhesive, the viscosity of the adhesive is too low, resulting in bleeding easily during screen printing or rotary printing, making it difficult to achieve accurate printing.
Polyvinyl acetal resin with specific structural units, which includes a hydrogenated carbon group with a number of carbon atoms between 4 and 20, with a total ether group content of 69% or more, and has a lower average molecularity (less than 2300) to improve the viscosity and taper properties of the adhesive.
The viscosity and taper properties of the conductive powder adhesive are significantly improved, the bleeding phenomenon during the printing process is prevented, and the accuracy and stability of printing are improved.
Smart Images

Figure 0007667902000001 
Figure 0007667902000002 
Figure 0007667902000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyvinyl acetal resin, a conductive paste, and a multilayer ceramic capacitor. [Background technology]
[0002] Multilayer electronic components such as multilayer circuit boards, multilayer coils, and multilayer ceramic capacitors are widely used. Among them, multilayer ceramic capacitors are generally manufactured through the following process. First, a ceramic raw material powder is added to a solution in which a binder resin such as polyvinyl butyral resin or poly(meth)acrylic acid ester resin is dissolved in an organic solvent, and the mixture is mixed uniformly to obtain a ceramic slurry composition. The slurry composition is cast onto a support, and volatile matters such as the solvent are removed by heating or the like, and then the ceramic green sheet is peeled off from the support to obtain a ceramic green sheet. Next, the ceramic green sheets obtained are coated with a conductive paste for internal electrodes by screen printing or gravure printing, and multiple sheets are alternately stacked and heated and pressed to produce a laminate. After that, a process for thermally decomposing and removing binder resin components and the like contained in the laminate, known as a degreasing process, is performed, and external electrodes are sintered onto the end faces of the ceramic sintered body obtained by firing to produce a multilayer ceramic capacitor.
[0003] The conductive paste for the internal electrodes is obtained by kneading a conductive powder, an organic solvent, and a binder resin, such as ethyl cellulose or polyvinyl acetal resin. However, when a polyvinyl acetal resin is used as the binder resin, there is a problem in that stringiness occurs when the paste is printed by screen printing. In order to solve the above problems, Patent Document 1 discloses a conductive paste containing a carboxylic acid-modified polyvinyl acetal resin, an organic solvent, and a conductive powder. In addition, Patent Document 2 discloses a conductive paste containing a polyvinyl acetal resin having an ethylene group in order to solve the above problems. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-228780 A [Patent Document 2] JP 2008-285590 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, the miniaturization of multilayer ceramic capacitors has been attracting attention, and as a result, more precise printability is required for the conductive paste for internal electrodes. However, when the polyvinyl acetal resin described in Patent Document 1 or 2 is used as a binder resin for the conductive paste for internal electrodes, the viscosity of the paste after kneading with the conductive powder is low, and bleeding of the conductive paste for internal electrodes may occur when screen printing or gravure printing is performed.
[0006] An object of the present invention is to provide a polyvinyl acetal resin that has high paste viscosity after being kneaded with a conductive powder, has good thixotropy, and is excellent in printability, and to provide a conductive paste and a multilayer ceramic capacitor each using the polyvinyl acetal resin. Here, the printability means that both stringiness and bleeding during screen printing or gravure printing can be prevented. [Means for solving the problem]
[0007] The present disclosure 1 has a constitutional unit represented by the following formula (1), and R 1 is a hydrocarbon group having 4 to 20 carbon atoms, the total amount of acetal groups is 69 mol % or more, and the average degree of polymerization is less than 2,300. [ka] This disclosure 2 is a 10 mass% solution dissolved in dihydroterpineol acetate (DHTA) solvent, measured at a temperature of 20°C and in a shear region of 100 s -1 The polyvinyl acetal resin according to Disclosure 1 has a viscosity of 1.5 Pa·s or more when measured using a rotational rheometer under the following conditions: The present disclosure 3 relates to R in the formula (1). 1 is a hydrocarbon group having 6 to 20 carbon atoms, and the amount of acetyl groups is 5 mol % or less. The present disclosure 4 relates to R 1 is a linear hydrocarbon group having 6 or 9 carbon atoms. The present disclosure 5 is the polyvinyl acetal resin according to any one of the present disclosures 1 to 4, wherein the content of the constitutional unit represented by the formula (1) is 5 mol % or more and 35 mol % or less. The present disclosure 6 is a polyvinyl acetal resin according to any one of the present disclosures 1 to 5, in which the content of the structural unit represented by formula (1) relative to the total amount of acetal groups (content of the structural unit represented by formula (1) / total amount of acetal groups) is 0.06 or more and 0.51 or less. The present disclosure 7 is the polyvinyl acetal resin according to any one of the present disclosures 1 to 6, in which the amount of hydroxyl groups is 10 mol % or more and 30 mol % or less. The present disclosure 8 is the polyvinyl acetal resin according to any one of the present disclosures 1 to 7, which has an average degree of polymerization of 500 or more. The present disclosure 9 is a conductive paste containing the polyvinyl acetal resin according to any one of the present disclosures 1 to 8, an organic solvent, a conductive powder, and a dispersion improver. The present disclosure 10 is a multilayer ceramic capacitor formed using the conductive paste according to the present disclosure 9.
[0008] Means for Solving the Problems The present inventors have, as a result of extensive research, found that a polyvinyl acetal resin containing a specific structural unit and having a total acetal group content within a specified range has a high paste viscosity after being kneaded with a conductive powder, good thixotropy, and excellent printability, and have thus completed the present invention.
[0009] The polyvinyl acetal resin of the present invention has a constitutional unit represented by the following formula (1), 1 is a hydrocarbon group having a carbon number of 4 to 20. By having such a hydrocarbon group, it is possible to achieve excellent solubility in a solvent, high paste viscosity, and good thixotropy, and thus good printability.
[0010] [ka]
[0011] Above R 1 The number of carbon atoms in R is preferably 5 or more. The lower limit of the number of carbon atoms is more preferably 6, the upper limit is more preferably 15, and the upper limit is more preferably 10. 1 may be a combination of two or more hydrocarbon groups having different carbon numbers.
[0012] Above (R 1 As the hydrocarbon group having 4 to 20 carbon atoms, an alkyl group having 4 to 20 carbon atoms is preferable. Examples of the alkyl group having 4 to 20 carbon atoms include a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, a hexadecyl group, a heptadecyl group, an octadecyl group, a nonadecyl group, and an eicosyl group.
[0013] Above (R 1 The hydrocarbon group having 4 to 20 carbon atoms (a) may be a linear alkyl group or a branched alkyl group. Examples of the linear alkyl group include an n-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, an n-nonyl group, an n-decyl group, an n-undecyl group, an n-dodecyl group, an n-tridecyl group, an n-tetradecyl group, an n-hexadecyl group, an n-heptadecyl group, an n-octadecyl group, an n-nonadecyl group, and an n-eicosyl group. Among them, the above R 1 is preferably a linear hydrocarbon group having 6 or 9 carbon atoms, and is preferably an n-hexyl group or an n-nonyl group. By having such a hydrocarbon group, it is possible to obtain excellent solubility in solvents, high paste viscosity, and good thixotropy, and thus good printability.
[0014] Examples of the branched alkyl group include isobutyl, isopentyl, neopentyl, 1-methylhexyl, 1-methylheptyl, 1-methyloctyl, 1-methylnonyl, 1-methyldecyl, 1-methylundecyl, and 1-methyldodecyl groups. Other examples include 1-methyltridecyl, 1-methyltetradecyl, 1-methylheptadecyl, 1-methylhexadecyl, 1-methylpentadecyl, 1-methyloctadecyl, and 1-methylnonadecyl groups. Further examples include alkyl groups in which an alkyl group having 2 or more carbon atoms is substituted at the carbon atom at position 1 (for example, 1-ethyldecyl group, 1-propylnonyl group, 1-butyloctyl group, 1-pentylheptyl group, 1-octyldecyl group, etc.). In addition, in the branched alkyl group, the branched position is not limited to the carbon atom at the first position, but may be the carbon atom at the second position or higher. For example, examples of the alkyl group in which a methyl group is substituted at the carbon atom at the second position or higher include 2-methylundecyl, 3-methylundecyl, and 4-methylundecyl groups. Examples of the alkyl group in which an alkyl group having 2 or more carbon atoms is substituted at the carbon atom at the second position or higher include 2-ethylhexyl, 2-ethylheptyl, 2-ethyloctyl, 2-ethylundecyl, 2-ethyloctadecyl, 2-propylundecyl, 2-butylundecyl, and 2-octylundecyl groups. Further examples include 3-ethylundecyl, 4-ethyloctadecyl, 4-butyloctadecyl, and neodecyl groups.
[0015] In the present invention, the hydrocarbon group having 4 to 20 carbon atoms is preferably a linear alkyl group. The alkyl group having 4 to 20 carbon atoms may be composed of two or more alkyl groups including a linear alkyl group and a branched alkyl group, or may be composed of only linear alkyl groups. 1 may be an alkyl group based on a bio-derived aldehyde having 4 or more carbon atoms.
[0016] The content of the structural unit represented by the above formula (1) in the polyvinyl acetal resin of the present invention is preferably 5 mol% at the lower limit, more preferably 10 mol% at the lower limit, and preferably 35 mol% at the upper limit, more preferably 33 mol% at the upper limit. This allows for excellent solubility in solvents, high paste viscosity, good thixotropy, and good printability. The content of the structural unit represented by the above formula (1) is 1 H-NMR and 13 It is measured using C-NMR (nuclear magnetic resonance spectroscopy).
[0017] The polyvinyl acetal resin of the present invention preferably further has an acetal unit represented by the following formula (2) different from the constitutional unit represented by the above formula (1). By having the acetal unit represented by the following formula (2), it is possible to obtain excellent solubility in a solvent, high paste viscosity, and good thixotropy, and to obtain good printability.
[0018] [ka] In formula (2), R 2 represents an alkyl group having 1 to 19 carbon atoms.
[0019] Examples of the alkyl group having 1 to 19 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, a hexadecyl group, a heptadecyl group, an octadecyl group, and a nonadecyl group. The alkyl group having 1 to 19 carbon atoms may be linear or branched. As for the alkyl group having 1 to 19 carbon atoms, the same ones as in the case of the alkyl group having 4 or more and 20 or less carbon atoms can be used. Among them, the above R 2 is preferably a linear hydrocarbon group having 1 or 3 carbon atoms, and is preferably a methyl group or an n-propyl group. By having such a hydrocarbon group, the solubility in a solvent can be improved.
[0020] The content of the acetal unit represented by the above formula (2) in the polyvinyl acetal resin of the present invention is preferably 34 mol% at the lower limit, more preferably 36 mol% at the lower limit, and preferably 85 mol% at the upper limit, more preferably 80 mol% at the upper limit. By setting the content of the acetal unit represented by the above formula (2) within the above range, it is possible to obtain excellent solubility in solvents, high paste viscosity, good thixotropy, and good printability. The content of the acetal unit represented by the above formula (2) is1 H-NMR and 13 It is measured using C-NMR (nuclear magnetic resonance spectroscopy).
[0021] When the polyvinyl acetal resin of the present invention contains the acetal unit represented by the above formula (1) and the acetal unit represented by the above formula (2), the total content thereof is preferably 69 mol% at the lower limit, more preferably 71 mol% at the lower limit, and preferably 90 mol% at the upper limit, more preferably 80 mol% at the upper limit. By setting the total content within the above range, the resin has excellent solubility in a solvent, high paste viscosity, good thixotropy, and good printability.
[0022] When the polyvinyl acetal resin of the present invention contains the acetal unit represented by the above formula (1) and the acetal unit represented by the above formula (2), the ratio between them (the content of the acetal unit represented by the formula (1) / the content of the acetal unit represented by the formula (2)) is preferably 0.06 or more and 1.03 or less. By setting the ratio within the above range, the resin has excellent solubility in a solvent, high paste viscosity, good thixotropy, and good printability.
[0023] The total acetal group content (total amount of all acetal units) of the polyvinyl acetal resin of the present invention is preferably 69 mol% or more. By setting the total acetal group content within the above range, it is possible to obtain excellent solubility in solvents, high paste viscosity, good thixotropy, and good printability. The lower limit of the total acetal group content is preferably 69 mol%, more preferably 71 mol%, and the upper limit is preferably 90 mol%, more preferably 80 mol%. 1 H-NMR and 13 It is measured using C-NMR (nuclear magnetic resonance spectroscopy). The content of the structural unit represented by the above formula (1) relative to the total amount of acetal groups (content of the structural unit represented by the formula (1) / total amount of acetal groups) has a preferred lower limit of 0.06 and an upper limit of 0.51.
[0024] The polyvinyl acetal resin of the present invention has a structural unit having a hydroxyl group. The content of the hydroxyl group-containing structural unit (hydroxyl group amount) in the polyvinyl acetal resin of the present invention is preferably 10 mol % or more and 30 mol % or less. By keeping it within the above range, the solubility in a solvent can be improved. The more preferred lower limit of the amount of hydroxyl groups is 20 mol %, and the more preferred upper limit is 29 mol %. 1 H-NMR and 13 It is measured using C-NMR (nuclear magnetic resonance spectroscopy).
[0025] The polyvinyl acetal resin of the present invention has a structural unit having an acetyl group. The content of the structural unit having the acetyl group (acetyl group amount) in the polyvinyl acetal resin of the present invention is preferably 0.1 mol% at the lower limit and 10 mol% at the upper limit. By making the acetyl group amount 0.1 mol% or more, the solubility in the solvent can be improved, and by making the acetyl group amount 10 mol% or less, the solubility in the solvent can be improved. The more preferable lower limit of the acetyl group amount is 0.3 mol%, and the more preferable upper limit is 5 mol%. The amount of acetyl groups is 1 H-NMR and 13 It is measured using C-NMR (nuclear magnetic resonance spectroscopy).
[0026] The polyvinyl acetal resin of the present invention may have a structural unit having a carboxylic acid. The content of the structural unit having the carboxylic acid in the polyvinyl acetal resin of the present invention (amount of modification with carboxylic acid) is preferably 0.1 mol% at the lower limit and 10 mol% at the upper limit. By making the amount of the carboxylic acid group 0.1 mol% or more, the paste viscosity can be increased, and by making the amount of modification with carboxylic acid 10 mol% or less, the solubility in the solvent can be improved. The more preferable lower limit of the amount of the acetyl group is 0.3 mol%, and the more preferable upper limit is 5 mol%. The amount of carboxylic acid modification is1 H-NMR and 13 It is measured using C-NMR (nuclear magnetic resonance spectroscopy).
[0027] The polyvinyl acetal resin of the present invention has an average degree of polymerization of less than 2300. This makes it possible to improve the solubility in a solvent and to improve the thixotropy. The preferred lower limit of the average polymerization degree of the polyvinyl acetal resin of the present invention is 500, preferably less than 2300. When the average polymerization degree is 500 or more, industrial production is easy. When the average polymerization degree is less than 2300, the solubility in a solvent can be improved and the thixotropy is good. The more preferred lower limit of the average polymerization degree is 800, and the more preferred upper limit is 2000. The average polymerization degree of the polyvinyl acetal resin can be determined from the polyvinyl alcohol used as a raw material.
[0028] The polyvinyl acetal resin of the present invention may be copolymerized with an ethylenically unsaturated monomer within a range that does not impair the effects of the present invention. The ethylenically unsaturated monomer is not particularly limited, and examples thereof include acrylic acid, methacrylic acid, (anhydrous) phthalic acid, (anhydrous) maleic acid, (anhydrous) itaconic acid, etc. In addition, examples thereof include acrylonitrile, methacrylonitrile, acrylamide, methacrylamide, trimethyl-(3-acrylamido-3-dimethylpropyl)-ammonium chloride, acrylamido-2-methylpropanesulfonic acid and its sodium salt, etc. In addition, examples thereof include ethyl vinyl ether, butyl vinyl ether, N-vinylpyrrolidone, vinyl chloride, vinyl bromide, vinyl fluoride, vinylidene chloride, vinylidene fluoride, tetrafluoroethylene, sodium vinyl sulfonate, sodium allyl sulfonate, etc. Also usable is a terminal-modified polyvinyl alcohol obtained by copolymerizing a vinyl ester monomer such as vinyl acetate with ethylene in the presence of a thiol compound such as thiolacetic acid or mercaptopropionic acid, and then saponifying the copolymer.
[0029] The polyvinyl acetal resin of the present invention is dissolved in a 10% by weight solution of DHTA solvent, and the measurement temperature is 20° C., and the shear region is 100 s -1 It is preferable that the viscosity is 1.5 Pa s or more when measured using a rotational rheometer under the conditions of 1.5 Pa s or more. By setting the viscosity within the above range, a conductive paste with high paste viscosity and excellent printability can be produced. The viscosity is more preferably 10 Pa·s or more, and is preferably 100 Pa·s or less, and more preferably 50 Pa·s or less. The viscosity can be measured, for example, using a modular compact rheometer (MCR702e) manufactured by Anton Paar Co., Ltd. In addition, it is preferable to appropriately adjust the rotor during viscosity measurement, and the viscosity can be measured using a cone plate (Measuring cone CP50-1, D: 50 mm; Angle 1°).
[0030] The viscosity can be adjusted by the method and reaction conditions of the acetalization reaction when producing the polyvinyl acetal resin, the degree of polymerization of the polyvinyl acetal resin, the amount of hydroxyl groups, the amount of acetal groups, the amount of acetyl groups, the structure of the acetal unit (the number of carbon atoms in the alkyl group), the type and content of the modifying group, and the like.
[0031] Examples of methods for producing the polyvinyl acetal resin include a method of acetalizing polyvinyl alcohol with an aldehyde, and a method of acetalizing a polyvinyl acetal resin having an acetal unit represented by the above formula (1) with an aldehyde having 5 to 21 carbon atoms. In particular, it is preferable to use a method of acetalizing polyvinyl alcohol with at least one aldehyde having 5 to 21 carbon atoms. By using such a production method, the viscosity can be adjusted.
[0032] The method of acetalizing the polyvinyl alcohol with at least one aldehyde having 5 to 21 carbon atoms includes a method of preparing aldehydes having different carbon numbers, and then acetalizing the aldehydes to introduce acetal units having multiple alkyl groups having different carbon numbers. When producing the polyvinyl acetal resin, the acetalization may be carried out in the presence of a dispersant. More specifically, a method of introducing the acetal unit represented by the above formula (1) by acetalizing polyvinyl alcohol not having the acetal unit represented by the above formula (1) with a specific aldehyde can be mentioned.
[0033] The polyvinyl alcohol can be obtained, for example, by saponifying a vinyl ester polymer. Examples of the vinyl ester include vinyl formate, vinyl acetate, vinyl propionate, vinyl pivalate, etc. Among them, vinyl acetate is preferable from the viewpoint of economic efficiency.
[0034] The polyvinyl alcohol preferably has a degree of saponification of 85 mol % or more. The saponification degree is preferably 90 mol % or more and 99.9 mol % or less, and more preferably 95 mol % or more and 99.4 mol % or less. That is, the saponification degree is preferably 90 to 99.9 mol %, and more preferably 95 to 99.4 mol %.
[0035] In the method of reacting polyvinyl alcohol with an aldehyde having 5 to 21 carbon atoms, the aldehyde used in the acetalization reaction is not particularly limited, and examples thereof include linear aliphatic aldehydes and branched aliphatic aldehydes having 5 to 21 carbon atoms. Examples of the aliphatic aldehyde having 5 to 21 carbon atoms include valeraldehyde, hexylaldehyde, 2-ethylbutyraldehyde, 2-ethylhexylaldehyde, heptylaldehyde, octylaldehyde, nonylaldehyde, decylaldehyde, undecylaldehyde, dodecylaldehyde, tridecylaldehyde, tetradecylaldehyde, pentadecylaldehyde, hexadecylaldehyde, heptadecylaldehyde, octadecylaldehyde, eicosylaldehyde, heneicosylaldehyde, trimethylhexylaldehyde, methyloctylacetaldehyde, and methylnonylacetaldehyde. These aldehydes may be used alone or in combination of two or more. In particular, it is preferable to use an aldehyde having 5 to 21 carbon atoms in combination with an aldehyde having 4 or less carbon atoms. Among them, acetaldehyde, butylaldehyde, decylaldehyde, and heptaldehyde are preferable as the aldehyde.
[0036] The amount of the aldehyde to be added can be appropriately set according to the amount of acetal groups in the target polyvinyl acetal resin. In particular, it is preferable to add 5 mol% or more and 120 mol% or less, more preferably 10 mol% or more and 110 mol% or less, based on 100 mol% of polyvinyl alcohol, because the acetalization reaction is efficiently carried out and unreacted aldehyde is easily removed. That is, the amount of the aldehyde to be added is preferably 5 to 120 mol%, more preferably 10 to 110 mol%.
[0037] In the acetalization step, an aldehyde having a cyclic aliphatic group or an aromatic group may be used in combination with the aldehyde having 5 to 21 carbon atoms. Examples of the aldehyde having an aromatic group include benzaldehyde, cinnamaldehyde, 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, p-hydroxybenzaldehyde, m-hydroxybenzaldehyde, phenylacetaldehyde, and β-phenylpropionaldehyde.
[0038] In the above acetalization step, when an aldehyde having 5 or more carbon atoms is contained, a dispersing agent may or may not be used. In addition, in the acetalization step, it is preferable to use a method in which the polyvinyl acetal resin is reacted in a state in which it is precipitated during the acetalization reaction (precipitation method) compared to a method in which the polyvinyl acetal resin is reacted in a dissolved state (dissolution method) in the acetalization reaction. Furthermore, when the acetalization is performed using the dispersant, it is preferable to use the precipitation method.
[0039] Examples of the dispersing agent include sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, colloidal silica, polyoxyethylene polyoxypropylene cetyl ether, polyoxyethylene polyoxypropylene lauryl ether, etc. These dispersing agents may be used alone or in combination of two or more. Among them, sodium dodecylbenzenesulfonate and polyoxyethylene polyoxypropylene cetyl ether are preferred.
[0040] The above acetalization reaction is preferably carried out in the presence of an acid catalyst. The acid catalyst includes, for example, mineral acids, carboxylic acids, sulfonic acids, and the like. Examples of the mineral acid include sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid. Examples of the carboxylic acid include formic acid, acetic acid, and propionic acid. Examples of the sulfonic acid include paratoluenesulfonic acid, methanesulfonic acid, ethanesulfonic acid, and benzenesulfonic acid. These acid catalysts may be used alone or in combination of two or more. Among them, paratoluenesulfonic acid and hydrochloric acid are preferred.
[0041] The temperature at which the aldehyde is added (aldehyde introduction temperature) is preferably 0°C or higher, more preferably 5°C or higher, and is preferably 70°C or lower. The temperature when the catalyst is added is preferably 5°C or higher and 50°C or lower. The retention time in the acetalization reaction is preferably 0.5 hours or more and 5 hours or less, and more preferably 1 hour or more and 3 hours or less. The temperature maintained in the acetalization reaction is preferably 0°C or higher and 65°C or lower, and more preferably 5°C or higher and 60°C or lower.
[0042] Applications of the polyvinyl acetal resin of the present invention include, for example, binders and dispersants for conductive pastes, battery electrodes, secondary battery electrodes, etc., modifiers for adhesives based on epoxy resins, phenol resins, etc., ceramic green sheets, etc. In particular, when the polyvinyl acetal resin of the present invention is used as a conductive paste, the paste has high viscosity after being kneaded with a conductive powder, and has good thixotropy, making it possible to obtain a paste with excellent printability.
[0043] The present invention also includes a conductive paste containing the polyvinyl acetal resin of the present invention, an organic solvent, a conductive powder, and a dispersion improver.
[0044] As the organic solvent, an organic solvent generally used in conductive pastes can be used. Examples of the organic solvent include terpineol derivatives such as dihydroterpineol, terpinyl acetate, isobornyl acetate, dihydroterpinyl acetate, dihydroterpinyl methyl ether, and terpinyl methyl ether, hydrocarbon solvents such as mineral spirits, and ethers and esters such as dipropylene glycol monomethyl ether and dipropylene glycol monomethyl ether acetate. Among these, dihydroterpineol and dihydroterpinyl acetate are preferred. These organic solvents may be used alone or in combination of two or more.
[0045] The amount of the organic solvent is not particularly limited, but the preferred lower limit is 100 parts by weight and the preferred upper limit is 10,000 parts by weight relative to 100 parts by weight of the polyvinyl acetal resin. When the amount of the organic solvent is 100 parts by weight or more, the viscosity of the conductive paste can be set in a suitable range, and printability can be improved. When the amount of the organic solvent is 10,000 parts by weight or less, the performance of the polyvinyl acetal resin can be fully exhibited in the conductive paste. The more preferred lower limit of the amount of the organic solvent relative to 100 parts by weight of the polyvinyl acetal resin is 200 parts by weight and the more preferred upper limit is 5,000 parts by weight.
[0046] The conductive powder is not particularly limited, and examples thereof include powders made of nickel, aluminum, silver, copper, and alloys thereof. These conductive powders may be used alone or in combination of two or more. Among these, nickel is preferred because of its excellent conductivity.
[0047] The conductive powder preferably has an average particle size of 50 to 300 nm and is substantially spherical in shape. When the average particle size is 50 nm or more, the conductive powder has a suitable specific surface area and can improve the dispersibility of the conductive powder. When the average particle size is 300 nm or less, the surface smoothness after printing can be improved. Note that substantially spherical includes particles having a shape close to a sphere as well as a perfect sphere.
[0048] The amount of the conductive powder to be blended is not particularly limited, but a preferred lower limit is 100 parts by weight and a preferred upper limit is 10,000 parts by weight per 100 parts by weight of the polyvinyl acetal resin. When the amount of the conductive powder is 100 parts by weight or more, the density of the conductive powder in the conductive paste can be kept in a sufficient range, and the conductive paste can have excellent conductivity. When the amount of the conductive powder is 10,000 parts by weight or less, the dispersibility of the conductive powder in the conductive paste can be improved, and the conductive paste can have excellent printability. The more preferred lower limit of the blending amount of the conductive powder is 200 parts by weight, and the more preferred upper limit is 5,000 parts by weight, relative to 100 parts by weight of the polyvinyl acetal resin.
[0049] The conductive paste preferably further contains a ceramic powder in addition to the conductive powder, which makes it easier to match the shrinkage behavior of the conductive powder during firing with that of the ceramic green sheets. The ceramic powder is not particularly limited, but is preferably barium titanate, which is used in the green sheet. The average particle size of the ceramic powder is not particularly limited, but is preferably smaller than the average particle size of the conductive powder, specifically, is preferably 30 nm to 200 nm.
[0050] The dispersion improver is not particularly limited, but for example, fatty acids, aliphatic amines, alkanolamides, and phosphoric esters are suitable. In addition, a silane coupling agent or the like may be added. The fatty acid is not particularly limited, and examples thereof include saturated fatty acids such as behenic acid, stearic acid, palmitic acid, myristic acid, lauric acid, capric acid, caprylic acid, coconut fatty acid, etc., and unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, sorbic acid, beef tallow fatty acid, and hardened castor fatty acid, etc. Among these, lauric acid, stearic acid, oleic acid, etc. are preferred. The aliphatic amine is not particularly limited, and examples thereof include laurylamine, myristylamine, cetylamine, stearylamine, oleylamine, alkyl(coconut)amine, alkyl(hardened beef tallow)amine, alkyl(beef tallow)amine, and alkyl(soybean)amine. The alkanolamide is not particularly limited, and examples thereof include coconut fatty acid diethanolamide, beef tallow fatty acid diethanolamide, lauric acid diethanolamide, and oleic acid diethanolamide. The phosphate ester is not particularly limited, and examples thereof include polyoxyethylene alkyl ether phosphate ester and polyoxyethylene alkyl allyl ether phosphate ester.
[0051] The conductive paste may contain appropriate additives such as a plasticizer, a lubricant, an antistatic agent, and a surfactant, as long as the effects of the present invention are not impaired.
[0052] Examples of the plasticizer include phthalic acid diesters such as dioctyl phthalate (DOP) and dibutyl phthalate (DBP), adipic acid diesters such as dioctyl adipate, and alkylene glycol diesters such as triethylene glycol-di-2-ethylhexanoate, tetraethylene glycol-di-2-ethylhexanoate, triethylene glycol-di-2-ethylbutyrate, tetraethylene glycol-di-2-ethylbutyrate, tetraethylene glycol-di-heptanoate, and triethylene glycol-di-heptanoate.
[0053] The method for producing the conductive paste is not particularly limited, and examples thereof include a method in which the polyvinyl acetal resin, the conductive powder, the organic solvent, and various additives added as necessary are mixed using various mixers such as a ball mill, a blender mill, and a three-roll mill.
[0054] The conductive paste is applied to ceramic green sheets by a printing process, and a plurality of these sheets are stacked and heated and pressed to produce a laminate, which is then degreased and fired to produce a ceramic sintered body, and external electrodes are formed on the end faces of the ceramic sintered body to produce a multilayer ceramic capacitor. As the printing process, screen printing, die coating, gravure offset, etc. can be used. Such a multilayer ceramic capacitor also constitutes the present invention. The polyvinyl acetal resin of the present invention or the conductive paste of the present invention can also be suitably used as a multilayer ceramic capacitor. Furthermore, the multilayer ceramic capacitor of the present invention can be manufactured by carrying out the steps of applying the conductive paste of the present invention onto a ceramic green sheet, stacking a plurality of the ceramic green sheets and heat-pressing them to form a laminate, degreasing and firing to form a ceramic sintered body, and forming external electrodes on end faces of the ceramic sintered body. Effect of the Invention
[0055] According to the present invention, it is possible to provide a polyvinyl acetal resin that has a high paste viscosity after being mixed with a conductive powder, has good thixotropy, and is excellent in printability, and a conductive paste and a multilayer ceramic capacitor using the polyvinyl acetal resin. Also, according to the present invention, it is possible to provide a polyvinyl acetal resin that has excellent solvent solubility and adhesion, and a conductive paste and a multilayer ceramic capacitor using the polyvinyl acetal resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0056] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0057] Example 1 (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 99.2 mol% and an average polymerization degree of 1700 and 13.5 g of Unisafe 10P-8 (polyoxyethylene polyoxypropylene cetyl ether, manufactured by NOF Corporation) as a dispersant diluted with pure water to a concentration of 20% by mass were added to 1600 g of pure water and dissolved by stirring at 90°C for 2 hours. This solution was cooled to 65°C, and 70g of n-butyl aldehyde and 75g of n-decyl aldehyde were added. Then, it was cooled to 15°C, and 20g of hydrochloric acid with a concentration of 35% by mass was diluted with 180g of pure water and added. The liquid temperature was kept at 15°C and the acetalization reaction was carried out for 1 hour, and the reaction product was precipitated. After 1 hour of the acetalization reaction, 13.5g of sodium dodecylbenzenesulfonate (SDBS) with a concentration of 20% by mass dissolved in pure water was added, and the acetalization reaction was carried out for another 1 hour. Next, the temperature was raised to 45°C at a rate of 2 to 3°C / 5 minutes, and the liquid temperature was kept at 45°C for 3 hours to complete the reaction, and the reaction was neutralized, washed with water, and dried by a conventional method to obtain a powder of polyvinyl acetal resin (long-chain alkyl modified). The obtained polyvinyl acetal resin was dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, the amount of acetyl groups, and the amount of hydroxyl groups were measured using C-NMR (nuclear magnetic resonance spectrum). The total amount of acetal groups (the sum of the contents of each acetal unit) was calculated from the measured values. The results are shown in Table 1. The content of each acetal unit is as follows: 13 Quantitative analysis was performed using C-NMR. The acetal unit is a structural unit represented by the above formula (1) [R 1 =(CH2)8CH3] and the acetal unit [R 2 =(CH2)2CH3].
[0058] Example 2 (Preparation of polyvinyl acetal resin) A polyvinyl acetal resin powder was obtained in the same manner as in Example 1, except that 90 g of polyvinyl alcohol having a saponification degree of 99.1 mol% and an average polymerization degree of 1700 and 60 g of polyvinyl alcohol having a saponification degree of 98.2 mol% and an average polymerization degree of 800 were used instead of 150 g of polyvinyl alcohol having a saponification degree of 99.2 mol% and an average polymerization degree of 1700. The obtained polyvinyl acetal resin was dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13The content of each acetal unit, the amount of acetyl groups, and the amount of hydroxyl groups were measured using C-NMR (nuclear magnetic resonance spectrum). The total amount of acetal groups (the sum of the contents of each acetal unit) was calculated from the measured values. The results are shown in Table 1. The content of each acetal unit is as follows: 13 Quantitative analysis was performed using C-NMR. The acetal unit is a structural unit represented by the above formula (1) [R 1 =(CH2)8CH3] and the structural unit represented by the above formula (2) [R 2 =(CH2)2CH3].
[0059] Example 3 (Preparation of polyvinyl acetal resin) A polyvinyl acetal resin powder was obtained in the same manner as in Example 1, except that 150 g of polyvinyl alcohol having a saponification degree of 98.6 mol% and an average polymerization degree of 800 was used instead of 150 g of polyvinyl alcohol having a saponification degree of 99.2 mol% and an average polymerization degree of 1,700. The obtained polyvinyl acetal resin was dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, the amount of acetyl groups, and the amount of hydroxyl groups were measured using C-NMR (nuclear magnetic resonance spectrum). The total amount of acetal groups (the sum of the contents of each acetal unit) was calculated from the measured values. The results are shown in Table 1. The content of each acetal unit is as follows: 13 Quantitative analysis was performed using C-NMR. The acetal unit is a structural unit represented by the above formula (1) [R 1 =(CH2)8CH3] and the structural unit represented by the above formula (2) [R 2 =(CH2)2CH3].
[0060] Example 4 (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 99.1 mol% and an average polymerization degree of 1700 and 13.5 g of Unisafe 10P-8 (polyoxyethylene polyoxypropylene cetyl ether, manufactured by NOF Corporation) as a dispersant diluted with pure water to a concentration of 20% by mass were added to 1600 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 65°C, and 87g of n-butylaldehyde and 46g of n-heptaldehyde were added. After that, the solution was cooled to 15°C, and 20g of hydrochloric acid with a concentration of 35% by mass was diluted with 180g of pure water and added. The liquid temperature was kept at 15°C and the acetalization reaction was carried out for 1 hour, and the reaction product was precipitated. After 1 hour of the acetalization reaction, 13.5g of sodium dodecylbenzenesulfonate (SDBS) with a concentration of 20% by mass dissolved in pure water was added, and the acetalization reaction was carried out for another 1 hour. Next, the temperature was raised to 60°C at a rate of 2 to 3°C / 5 minutes, and the liquid temperature was kept at 60°C for 3 hours to complete the reaction, and the reaction was neutralized, washed with water, and dried by a conventional method to obtain a powder of polyvinyl acetal resin (long-chain alkyl modified). The obtained polyvinyl acetal resin was dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, the amount of acetyl groups, and the amount of hydroxyl groups were measured using C-NMR (nuclear magnetic resonance spectrum). The total amount of acetal groups (the sum of the contents of each acetal unit) was calculated from the measured values. The results are shown in Table 1. The content of each acetal unit is as follows: 13 Quantitative analysis was performed using C-NMR. The acetal unit is a structural unit represented by the above formula (1) [R 1 =(CH2)5CH3] and the structural unit represented by the above formula (2) [R 2 =(CH2)2CH3].
[0061] Comparative Example 1 (Preparation of polyvinyl acetal resin) 160 g of carboxylic acid-modified polyvinyl alcohol (itaconic acid-modified, carboxylic acid modification amount 0.5 mol%) with a saponification degree of 98.2 mol% and an average polymerization degree of 800 was added to 1700 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 120g of hydrochloric acid with a concentration of 35% by mass was added. Then, the solution was cooled to 15°C, and 9g of acetaldehyde and 110g of n-butylaldehyde were added to carry out an acetalization reaction and precipitate the reaction product. The liquid temperature was then kept at 50°C to complete the reaction for 4 hours, and the solution was neutralized, washed with water, and dried by a conventional method to obtain a polyvinyl acetal resin powder. The obtained polyvinyl acetal resin was dissolved in CDCl3 (chloroform), 1 The content of each acetal unit, the amount of acetyl groups, the amount of hydroxyl groups, and the amount of carboxylic acid modification were measured using H-NMR (nuclear magnetic resonance spectrum). The total amount of acetal groups (the sum of the contents of each acetal unit) was calculated from the measured values. The content of each acetal unit was calculated as follows: 13 Quantitative analysis was performed using C-NMR, and the results are shown in Table 1. The acetal units were acetoacetal units and butyral units.
[0062] Comparative Example 2 (Preparation of polyvinyl acetal resin) 170 g of polyvinyl alcohol having a saponification degree of 95.0 mol % and an average polymerization degree of 800 was added to 1700 g of pure water, and dissolved by stirring at 90° C. for 2 hours. The solution was cooled to 40°C, and 120 g of hydrochloric acid with a concentration of 35% by mass was added. Then, the solution was cooled to 10°C, and 130 g of n-butyl aldehyde was added to carry out an acetalization reaction and precipitate the reaction product. The liquid temperature was then kept at 30°C to complete the reaction for 6 hours, and the solution was neutralized, washed with water, and dried by a conventional method to obtain a polyvinyl acetal resin powder. The obtained polyvinyl acetal resin was dissolved in CDCl3 (deuterated chloroform), 1 The content of each acetal unit, the amount of acetyl groups, and the amount of hydroxyl groups were measured using H-NMR (nuclear magnetic resonance spectrum). The total amount of acetal groups (the sum of the contents of each acetal unit) was calculated from the measured values. The results are shown in Table 1. The acetal unit was a butyral unit.
[0063] Comparative Example 3 (Preparation of polyvinyl acetal resin) 160 g of carboxylic acid-modified polyvinyl alcohol (itaconic acid-modified, carboxylic acid modification amount 0.2 mol%) with a saponification degree of 98.4 mol% and an average polymerization degree of 1700 was added to 1700 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 100 g of hydrochloric acid with a concentration of 35% by mass was added. Then, the solution was cooled to 10°C, and 120 g of n-butyl aldehyde was added to carry out an acetalization reaction and precipitate the reaction product. The liquid temperature was then kept at 40°C to complete the reaction for 6 hours, and the solution was neutralized, washed with water, and dried by a conventional method to obtain a polyvinyl acetal resin powder. The obtained polyvinyl acetal resin was dissolved in CDCl3 (deuterated chloroform), 1 The content of each acetal unit, the amount of acetyl groups, the amount of hydroxyl groups, and the amount of carboxylic acid modification were measured using H-NMR (nuclear magnetic resonance spectrum). The total amount of acetal groups (the sum of the contents of each acetal unit) was calculated from the measured values. The results are shown in Table 1. The acetal unit was a butyral unit.
[0064] <Evaluation> The obtained polyvinyl acetal resin was evaluated as follows. (1) Resin viscosity (solution viscosity) measurement The obtained polyvinyl acetal resin was dissolved in dihydroterpinyl acetate solvent to a concentration of 10% by mass to prepare a sample for viscosity measurement. The viscosity of the obtained sample for viscosity measurement was measured using a rotational rheometer. The rotational rheometer used was a modular compact rheometer (MCR702e) (manufactured by Anton Paar), with a measurement temperature of 20°C and a shear range of 100 s -1 The measurements were performed using a rotor: cone plate (Measuring cone CP50-1, D: 50 mm; Angle 1°) under the above conditions.
[0065] (2) Solvent solubility Polyvinyl acetal resin and dihydroterpinyl acetate were mixed in a sealed glass container so that the polyvinyl acetal resin was 10% by mass, and 30 g of a solution was prepared. The solution was mixed for 5 hours using a hot stirrer so that the temperature of the solution was 60°C, and the state of the solution immediately after mixing was visually observed and evaluated according to the following criteria. ◎: Completely dissolved 〇: Partially dissolved ×: Insoluble
[0066] (3) Paste viscosity measurement (a) Preparation of conductive paste A resin solution was obtained by dissolving 10 parts by weight of the polyvinyl acetal resin obtained in the Examples and Comparative Examples in 90 parts by weight of dihydroterpinyl acetate. After mixing 180 parts by weight of nickel powder as the conductive powder, 50 parts by weight of dihydroterpinyl acetate, and 0.1 parts by weight of oleic acid as a dispersion improver, the obtained resin solution was mixed and dispersed with a triple roll to obtain a conductive paste.
[0067] (b) Viscosity measurement The viscosity of the obtained conductive paste was measured using a rotational rheometer. The rotational rheometer used was a modular compact rheometer (MCR702e) (manufactured by Anton Paar), with a measurement temperature of 20°C and a shear range of 10 s -1 Measurements were carried out under the above conditions using a rotor: cone plate (Measuring cone CP25-2, D: 25 mm; Angle 2°) and were evaluated according to the following criteria. ◎: 20.0 Pa s or more ○: 14.0 Pa s or more, less than 20.0 Pa s ×: Less than 14.0 Pa s
[0068] (c) Thixotropy The obtained conductive paste was subjected to viscosity measurement using a rotational rheometer. As the rotational rheometer, a modular compact rheometer (MCR702e) (manufactured by Anton Paar) was used, and the measurement temperature was 20° C., the shear range was 100 s-1 The measurements were performed using a rotor: cone plate (Measuring cone CP25-2, D: 25mm; Angle 2°) under the condition of 10s. -1 The thixotropy was also measured under the conditions of 10s -1 Viscosity / 100s -1 The viscosity was evaluated according to the following criteria. ◎: 4.0 or higher ○: 2.5 or more, less than 4.0 ×: Less than 2.5
[0069] [Table 1] [Industrial Applicability]
[0070] According to the present invention, it is possible to provide a polyvinyl acetal resin that has a high paste viscosity after being kneaded with a conductive powder, has good thixotropy, and has excellent printability, as well as a conductive paste and a multilayer ceramic capacitor that use the polyvinyl acetal resin.
Claims
1. The compound has a constitutional unit represented by the following formula (1), and R 1 is a linear hydrocarbon group having 6 to 9 carbon atoms, the total amount of acetal groups is 69 mol % or more, the average degree of polymerization is less than 2,300, and the content of the structural unit represented by formula (1) relative to the total amount of acetal groups (the content of the structural unit represented by formula (1) / the total amount of acetal groups) is 0.06 or more and 0.51 or less. 【Chemistry 1】
2. A 10% by weight solution of dihydroterpineol acetate (DHTA) in a solvent was measured at a temperature of 20° C. and a shear region of 100 s. -1 2. The polyvinyl acetal resin according to claim 1, having a viscosity of 1.5 Pa·s or more when measured using a rotational rheometer under the following conditions:
3. A polyvinyl acetal resin described in claim 1 or 2, having an acetyl group content of 5 mol% or less.
4. R in the formula (1) 1 The polyvinyl acetal resin according to claim 1 or 2, wherein is a linear hydrocarbon group having 6 or 9 carbon atoms.
5. The polyvinyl acetal resin according to claim 1 or 2, wherein the content of the structural unit represented by the formula (1) is 5 mol % or more and 35 mol % or less.
6. 3. The polyvinyl acetal resin according to claim 1, wherein the amount of hydroxyl groups is from 10 mol % to 30 mol %.
7. The polyvinyl acetal resin according to claim 1 or 2, having an average degree of polymerization of 500 or more.
8. A conductive paste comprising the polyvinyl acetal resin according to claim 1 or 2, an organic solvent, a conductive powder, and a dispersion improver.
9. A multilayer ceramic capacitor comprising the conductive paste according to claim 8.
Citation Information
Patent Citations
Optical type information recording body
JP1985107390A
Interlayer for laminated glass having low autohesion property
JP1987278148A
Polyvinyl acetal resin and intermediate film for laminated glass
JP1992325503A
Intermediate film for laminated glass
JP1993330864A
Interliner for sound-insulating laminated glass and sound-insulating laminated glass produced by using the interliner
JP1994191905A